An Information System Model for One Tampon One Product Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research about an information system model for one Tampon one product management in Thai supply chain. The purpose of this research were to develop and to evaluate an information system model for one Tampon one product management in Thai supply chain.. A sample groups were five experts in supply chain , five experts in Information system . The paper sample totalling ten experts. The paper tool was evaluation form to evaluate an information system model for one Tampon one product management in Thai supply chain comprises seven components, namely main components, Supplier, OTOP firms, Outlet . wholesaler, Retailer, Customer .The data analysed by using arithmetic mean and standard deviation. an information system model for one Tampon one product management in Thai supply chain using Back-Box technique. The results from experts agreement of an information system model for one Tampon one product management in Thai supply chain. It showed that the model could be used to develop information system.